Risk factors of coronary disease in patients who have undergone myocardial revascularization - Francisca Elisângela Teixeira Lima; Thelma Leite de Araújo; Marcos Vinícius de Oliveira Lopes; Lucia de Fatima da Silva; Ana Ruth Macedo Monteiro; Sherida Karanini Paz de Oliveira (Rev Rene)
The objective was to determine the frequency of risk factors of coronary disease in patients who undergo myocardial revascularization. Descriptive study, developed in the Cardiology clinic of a public hospital, which is a reference in Fortaleza, Ceará, Brazil. The samples were collected from 78 patients who have undergone myocardial revascularization. Data were collected in records and assessments of the patient in hospital. Risk factors for coronary artery disease were: hypertension (83,3%), diabetes (46,2%), dyslipidemia (46,2%), obesity (67,9%), inactivity (57,7% ) and smoking (34,6%). We conclude that hypertension, obesity and inactivity were the most frequent risk factors in patients who have undergone myocardial revascularization and that most of them had at least three risk factors.